(untitled) (Al-Aasar, 2025)
The wives of the Prophet (peace be upon him) received education and training in various ways. Direct education from the Prophet (peace be upon him) was the main source of education. The Prophet (peace be upon him) provided personal guidance and instruction on various aspects. Learning and teaching the Quran was also an important part of life. The Prophet (peace be upon him) taught them the Quran and explained its meanings and interpretations. The wives observed the actions and behavior of the Prophet (peace be upon him) and learned from his example. They participated in religious rituals such as prayer and fasting with the Prophet (peace be upon him). They played a significant role in shaping Islamic history and thought.The education and knowledge of the wives of the Prophet ﷺ were of paramount importance in the transmission of Islamic teachings. They integrated knowledge into their personal lives and made it accessible to the entire Muslim community. This research study highlights how the wives of the Prophet ﷺ understood the significance of education and how they contributed to the dissemination of this knowledge to future generations. Their legacy serves as a guiding light for Muslims today.